The Effectiveness of Baby Massage on Sleep Duration for Infants Aged 1-12 Months - Nur Ain Desta Sulasdi; Ismarwati (Jurnal Penelitian Pendidikan IPA, 2023)
This scoping review aims to review the effectiveness of baby massage on sleep duration of infants aged 1-12 months. The criteria included in this review were articles in Indonesian or English with publications in the last 10 years, articles focused on infant massage and increasing sleep duration for infants aged 1-12 months. In Indonesia, some babies experience sleep problems, namely around 44.2% where almost all parents do not consider the disturbance experienced by babies as a problem with a total of 285 babies, data obtained from 51.3% of babies have sleep disturbances, 42.2% of babies sleep less than 9 hours a night, and at night the baby wakes up more than 3 times by waking up. more than an hour. The structure for writing this scoping review uses the PRISMA-ScR Checklist with 5 stages according to Arksey and O'Malley. An article search was conducted on December 23, 2022 using several databases including PubMed, Wiley Online library, National Library and science direct. Of the 422 articles obtained, there were 64 potentially relevant articles, ten of which met the inclusion criteria. presented with three themes of baby sleep quality, baby development, infantile colic. Conclusion: from several articles obtained during the search, it was found that baby massage can improve the quality and duration of baby sleep. In addition, baby massage is also one of the colic treatments experienced by babies.